Efficacy of Listening to Murattal in Reducing the Pain Experienced by ICU Patients - Purnawan, Iwan; Hidayat, Arif Imam; Sutrisna, Eman; Alivian, Galih Noor; Wirakhmi, Ikit Netra (Jurusan Keperawatan FIKES UNSOED, 2021)
Background: Pain is one of the main problems in patients with ICU. Inadequate handling can cause adverse effects such as unstable hemodynamics, trigger stress, and thus hinder the healing process. Non-pharmacological intervention is needed to help manage pain in patients with ICU. Purpose: This study aims to identify the effect of murottal listening to pain in ICU patients. Methods: This is a quasi-experiment with pre-test and post-test with control group design. The sampling technique was simple random sampling, consisting of 40 respondents divided into two groups. The Critical Pain Observation Tool (CPOT) is used to measure pain. Statistics using a paired t-test, Wilcoxon-test, and Mann Whitney. Results: Significant decreases in pain scores were observed in treatment groups of 4, 5 to 4,0; p = 0,013. In the control group, there was a significant decrease in pain scores from 4,8 to 4,3; p = 0,001. There was no significant difference between the median decrease in pain in the intervention group (0.001 (-1-2.0) and the control group (0.001 (0.001-1.0)) with p = 0.242. Conclusion: Murottal listening does not have a significant effect on pain in patients of ICU.